Combating Street Crimes through Non-Penal Approach in Criminology Perspective - Muhammad Irsyad Irman Putra; Kuswandi (Indonesian Journal Publisher, 2026)
This study was motivated by the increase in street crime, which has a direct impact on the community's sense of security and social order. The measures taken to combat street crime have been dominated by repressive and reactive penal approaches, which have not been effective in reducing crime rates in a sustainable manner and have not addressed the underlying criminogenic factors. From a criminological perspective, street crime is understood as a social phenomenon influenced by socio-economic conditions, weak social control, and low community participation. This study aims to analyse the effectiveness of existing street crime prevention measures and examine the relevance of non-penal approaches as a more comprehensive and humanistic prevention strategy. The research method used is descriptive analysis with a conceptual normative juridical approach. The research data consists of secondary data obtained through a literature study of scientific books, academic journals, and previous research results relevant to criminal policy and criminology. The data is analysed qualitatively to explain the relationship between social structure, crime causation factors, and street crime prevention policies. The results of the study show that the penal approach has not been effective in reducing crime in a sustainable manner. The non-penal approach has a strategic role through community empowerment, strengthening social control, improving socio-economic conditions, and environmental management. This study concludes that the balanced and sustainable integration of penal and non-penal approaches is an important prerequisite for realising equitable community protection and social order.